Survivors of tobacco-related diseases and advocacy for tobacco control. (24th January 2008) - Mathew, M; Goldstein, A O; Hampton, K
Abstract : Survivors and victims of tobacco-related diseases can and should play significant roles in tobacco control advocacy efforts. This article describes one example of how to successfully incorporate their talents into a statewide programme.